Improving Polyphenolic Thermal Stability of Aristotelia Chilensis Fruit Extract by Encapsulation Within Electrospun Cyclodextrin Capsules - Guarda-Moraga, A; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A (Blackwell Publishing Ltd, 2019)
Aristotelia chilensis berry, also known as maqui (MQ), has received an increased interest in the last years due to its high polyphenolic content and interesting biological activities. In this work, extractions of maqui fruit were carried out under water, ethanol and ethanol 50%. The hydroalcoholic extract presented the highest polyphenolic content, antioxidant, antimicrobial, and anti-tyrosinase properties, resulting the most promising extract to be part of a nutraceutical product. Subsequently, because some polyphenols, principally anthocyanins, are highly sensitive to thermal treatments, encapsulation of the most powerful extract was performed by electrospray. Hydroxypropyl-β-cyclodextrin (HPβCD) microcapsules containing increased amounts of maqui fruit extract were successfully electrosprayed. Morphological analysis revealed when maqui extract was incorporated at 30%, the distribution of particle diameters showed the most homogeneous ratio. Electrospun HPβCD capsules containing maqui extract, HPβCD/MQ, improved the thermal stability of MQ and preserved total phenolic content when exposed to high-temperature treatments. Practical applications: The interest of consumers toward the consumption of foods rich in polyphenols has grown during the last years. One of the main sources of polyphenols are berry fruits, and maqui is one of Chilean berries with highest polyphenolic content, mainly anthocyanins. This fruit has also shown interesting antioxidant, antimicrobial, and anti-tyrosinase activities that could contribute to the preservation of foods. The protection of these maqui fruit extract polyphenols through the encapsulation in zeina microparticles broadens the range of applications of this fruit in different applications and food formulations that involve high temperature thermal treatments, such as bakery and dairy products. © 2019 Wiley Periodicals, Inc.